In vivo Efficacy and Pharmacokinetics of Optimized Apidaecin Analogs - Schmidt, Rico; Knappe, Daniel; Wende, Elisabeth; Ostorházi, Eszter; Hoffmann, Ralf (Frontiers in Chemistry, 2017)
Proline-rich antimicrobial peptides (PrAMPs) represent promising alternative therapeutic options for the treatment of multidrug-resistant bacterial infections. PrAMPs are predominantly active against Gram-negative bacteria by inhibiting protein expression via at least two different modes of action, i.e., blocking the ribosomal exit tunnel of 70S ribosomes (oncocin-type binding) or inhibiting the assembly of the 50S ribosomal subunit (apidaecin-type binding). The in vivo efficacy and favorable biodistribution of oncocins confirmed the therapeutic potential of short PrAMPs for the first time, whereas the in vivo evaluation of apidaecins is still limited despite the promising efficacy of apidaecin-analog Api88 in an intraperitoneal murine infection model. Here, the in vivo efficacy of apidaecin-analog Api137 was studied, which rescued all NMRI mice from a lethal intraperitoneal infection with E. coli ATCC 25922 when administered three times intraperitoneal at doses of 0.6 mg/kg starting one hour after infection. When Api88 and Api137 were administered intravenous or intraperitoneal at doses of 5 and 20 mg/kg, their plasma levels were similarly low (<3 µg/mL) and fourfold lower than for oncocin-analog Onc72. This contradicted earlier expectation based on the very low serum stability of Api88 with a half-life time of only ~5 min compared to ~6 hrs and ~3 hrs for Api137 and Onc72, respectively. Pharmacokinetic data relying on a sensitive mass spectrometry method utilizing multiple reaction monitoring and isotope-labeled peptides revealed that Api88 and Api137 were present in blood, urine, and kidney, and liver homogenates at similar levels accompanied by the same major metabolites comprising residues 1-16 and 1-17. The pretended discrepancy was solved, when all peptides were incubated in peritoneal lavage. Api137 was rapidly degraded at the C-terminus, while Api88 was rather stable despite releasing the same degradation products. Onc72 was very stable explaining its higher plasma levels compared to Api88 and Api137 after intraperitoneal administration illuminating its good in vivo efficacy. The data indicate that the degradation of therapeutic peptides should be studied in serum and further body fluids. Moreover, the high efficacy in murine infection models and the fast clearance of Api88 and Api137 within ~60 min after intravenous and ~90 min after intraperitoneal injections indicate that